The Significance of Indication in the Thirtieth Part of the Holy Quran - Asst. Lect. Ilham Mohammed Ali Abdulameer (Global Scientific Publishing, 2024)
The study on the significance of indication in the thirtieth part of the Holy Quran reveals the profound messages of the Quranic text. It contributes to reinforcing religious and ethical concepts and encourages contemplation and reflection. One of the greatest benefits of delving into the significance of conventional terms is the expansion of minds and the derivation of rulings, which ultimately leads to correct fatwas.
Keywords: Significance of Indication; Holy Quran; Mohammed bin Abdulaziz